Futurama : Season 4 Disc 2 - Matt, Groening; John Di Maggio; Katey Sagal; Lauren Tom; Maurice LaMarche; Phil LaMarr; Tress MacNeille; Billy West (USA 20th Century Fox Television, 1999)
Phillip Fry is a 25-year-old pizza delivery boy whose life is going nowhere. When he accidentally freezes himself on December 31, 1999, he wakes up 1,000 years in the future and has a chance to make a fresh start. He goes to work for the Planet Express Corporation, a futuristic delivery service that transports packages to all five quadrants of the universe. His companions include the delivery ship's captain, Leela, a beautiful one-eyed female alien who kicks some serious butt, and Bender, a robot with very human flaws.
Fry, a pizza guy is accidentally frozen in 1999 and thawed out New Year's Eve 2999.
Languages: English Subtitles: Danish, English, Finnish, Norwegian, Swedish
Keywords: Comedy; SciFi; Animation -- Tv Series